Analysis of Determining the Surge Arrester Protective Distance for Protection on 60 MVA Power Transformers at the 150 KV Main Substation in Surabaya Barat - Reza Sarwo Widagdo; Gatut Budiono; Miftachun Nasichin (PROGRAM STUDI TEKNIK ELEKTRO, 2024)
Because it provides electrical energy to customers that require protection from lightning interference, the substation is a crucial location. An electrical equipment's defense against lightning strikes is provided by a lighting arrestor. The arrester should be placed as near to the transformer as feasible for optimal protection. In order to restrict the installation of arresters to safeguard equipment, the maximum distance for arrester installation must be established. This study only looks at one 60 MVA transformer in the Surabaya Barat Main Substation, and its goal is to determine the minimum amount of error in transformer protection. Based on the maximum possible surge arrester surge arrester jarak with a power transformer at the Surabaya Barat Main Substation, the maximum possible surge arrester distance is 8,135 meters. Based on surge arrester capability, the transformer may be protected from over voltage since the maximum voltage that can occur is just 150.83 kV, with the maximum voltage remaining below the transverse impulse drop of around 650 kV.